A Wave Splitter with Simple Structure Based on Biaxial Anisotropic Medium - Chushun Zhang; Hui Huang; Luchen Huang; Yaru Dong; Xiaoyu Liu (International Journal of Antennas and Propagation)
A TE/TM wave splitter based on biaxial anisotropic slab is designed. According to the total reflection and total transmission of TE/TM waves incident from isotropic medium into biaxial anisotropic medium, we propose a wave splitter with simple structure and little limitation on both constitutive parameters and incident angle. All the results are verified by simulation.